YuNü-Jian attenuates diabetes-induced cardiomyopathy: integrating network pharmacology and experimental validation - Wang, Wei; Liu, Ruixia; Zhu, Yingying; Wang, Lina; Tang, Yu; Dou, Baolei; Tian, Shuo; Wang, Furong (Frontiers in Endocrinology, 2023)
Diabetic cardiomyopathy (DCM) is one of the most prevalent complications of diabetes with complex pathogenesis. YuNü-Jian (YNJ) is a traditional Chinese medicinal formula widely used for diabetes with hypoglycemic and cardioprotective effects. To investigate the actions and mechanisms of YNJ against DCM which has never been reported, network pharmacology, molecular docking and animal experimental validation were jointly applied. First, a total of 32 main ingredients of YNJ were identified and 700 potential targets were screened to construct herb-compound-target network. Then 94 differentially expressed genes of DCM were identified from GEO database. After that, PPI network of DCM and YNJ were generated from which hub genes (SIRT1, Nrf2, NQO1, MYC and APP) were assessed by topology analysis. Next, functional and pathway analysis indicated that the candidate targets were enriched in response to oxidative stress and Nrf2 signaling pathway. Furthermore, molecular docking revealed strong affinity between core targets and active components of YNJ. Finally, type 2 diabetic model was employed and intervened with YNJ for 10 weeks. The results showed that YNJ obviously attenuated cardiac collagen accumulation and degree of fibrosis. Meanwhile, YNJ significantly upregulated protein expression of myocardial SIRT1, Nrf2 and NQO1. Collectively, our findings suggested that YNJ could effectively ameliorate cardiomyopathy induced by diabetes possibly through SIRT1/Nrf2/NQO1 signaling.